Trust in the teacher – signs, difficulties, attempts to undermine it - Miko-Giedyk, Justyna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Trust is an essential part of teacher’s work. Cooperation with pupils and parents, and working together for the benefit of the child and his/her comprehensive development would be extremely burdensome, if not impossible, without trust. Believing in the truthfulness of the teacher’s words, in the legitimacy of his/her actions and decisions is the basis of the school’s functioning as an institution. Therefore, any attempts to limit trust towards teachers are highly detrimental to the entire educational process. The article presents perspectives of trust towards teachers and examples of various situations that undermine the credibility of teachers, which adversely affects the relationship with pupils, parents, the effectiveness of educational processes, but also the evaluation of the professional group of teachers and the school as an institution.